Investigations on the Nonlinear Optical Properties of 0D, 1D, and 2D Boron Nitride Nanomaterials in the Visible Spectral Region - Stefanie Dengler; Bernd Eberle (Nanomaterials, 2023)
In recent years, boron nitride nanomaterials have attracted increasing attention due to their unique properties such as high temperature stability and high thermal conductivity. They are structurally analogous to carbon nanomaterials and can also be generated as zero-dimensional nanoparticles and fullerenes, one-dimensional nanotubes and nanoribbons, and two-dimensional nanosheets or platelets. In contrast to carbon-based nanomaterials, which have been extensively studied during recent years, the optical limiting properties of boron nitride nanomaterials have hardly been analysed so far. This work summarises a comprehensive study on the nonlinear optical response of dispersed boron nitride nanotubes, boron nitride nanoplatelets, and boron nitride nanoparticles using nanosecond laser pulses at 532 nm. Their optical limiting behaviour is characterised by means of nonlinear transmittance and scattered energy measurements and a beam profiling camera is used to analyse the beam characteristics of the transmitted laser radiation. Our results show that nonlinear scattering dominates the OL performance of all measured boron nitride nanomaterials. Boron nitride nanotubes show a large optical limiting effect, much stronger than the benchmark material, multi-walled carbon nanotubes, which makes them promising for laser protection applications.